An exceptional case of degenerative endometriosis of the uterine torus - Merviel, Philippe; Rebahi, Christie; James, Pandora; Kergastel, Isabelle; Bourhis‐Guizien, Fanny; Conan‐Charlet, Virginie; Derquin, Fanny; Hardy‐Bessard, Anne‐Claire; Dupré, Pierre‐François; Morcel, Karine (Clinical case reports, 2023)
There are less than ten cases of deep endometriosis degeneration in the literature. The duration of endometriosis, the ovarian stimulation, the perimenopause and the obesity exposes the woman to an increased risk of endometriosis degeneration. There are less than ten cases of deep endometriosis degeneration in the literature. The duration of endometriosis, the ovarian stimulation, the perimenopause and the obesity exposes the woman to an increased risk of endometriosis degeneration.